The Ali-Muawiya Conflict and the Kharijite Secession reexamined in the Light of Ibadite Sources - Veccia Vaglieri, Laura (Proceedings of the twenty second Congress of Orientalists: held in Istanbul, September 15th to 22nd, 1951, 1953)
Keywords: Fitnah

Traduzione di passi riguardanti il conflitto ʿAlī-Muʿāwiya e la secessione khārigita dal Kitāb al-Jawāhir di al-Barrādī - Veccia Vaglieri, Laura (Annali dell'Istituto Universitario Orientale di Napoli, 1953)
Translations with comments and annotations from: Barrādī: K. al-Jawāhir (lith., Cairo 1302/1884-5, 111-147) (1-73); Shammākhī: K. al-Siyar (Cairo 1301, 45-56) (74-87); Naṣr b. Muzāḥim al-Minqarī: Waqʿat Ṣiffīn (88-92); index of names and Arabic terms in Veccia Vaglieri 1952 and in this article (92-98).
Keywords: Barrādī; Abū ‘l-Qāsim b. Ibrāhīm al-; Fitnah